Seizures with abdominal pain—a case of porphyrias complicated with status epilepticus - Izza Rehan; Fatima Aslam; Iqra Manzoor (Journal of the Pakistan Medical Association, 2026)
Acute intermittent porphyria (AIP) is the most common type of porphyria, caused due to the deficiency of HMBS enzyme in the heme synthesis pathway. One of its infrequent and clinically challenging complications is status epilepticus. We present the case of a 14-year-old boy, who was previously misdiagnosed as having appendicitis and later presented with persistent abdominal pain and seizures that progressed to status epilepticus. Diagnostic workup for organic causes of seizures was unremarkable and a porphobilinogen spot test confirmed the diagnosis. He was treated with dextrose and electrolyte correction along with magnesium sulfate and Levetiracetam for seizure control. The patient had recovered fully on his fortnightly follow-up visit. Limited local literature and the disease's rarity underscores the significance of this case. Future studies should concentrate on developing new treatment approaches for this multifaceted disease, as well as increasing the diagnostic precision for AIP in individuals who present with seizures. Timely intervention can alleviate suffering and minimise hospitalisations. Keywords: Acute Intermittent Porphyria, Status epilepticus, Case report, Treatment, Levetiracetam, Seizures.